ANALISIS STRATEGI HARGA DALAM UPAYA UNTUK MENINGKATKAN PENJUALAN PADA PT HARAPAN SENTOSA RAYA BARABAI - Jumiati; Khairunisa (Fekon Uvaya Banjarmasin, 2018)
This study aims to determine the pricing strategy in an effort to boost sales at PT Harapan Sentosa Raya Barabai, Hulu Sungai Tengah.The analyzes were performed using the study variables and the sales price, and price indicators include price lists, rebates / discounts, payment periods and credit terms. This analysis using descriptive analysis techniques using qualitative data research, the data collected is in the form of words, pictures, and not numbers.The results showed that the pricing strategy undertaken by PT Harapan Sentosa Raya Barabai for this is to issue a price list, giving rebates / discounts, provide the payment period and credit terms for consumers, pricing strategy by PT Harapan Sentosa Raya Barabai needs to be improved, namely by give discounts for goods already old so quickly exhausted, and credit terms for consumers to do a deal to approve the purchase agreement with PT Harapan Sentosa Raya goods Barabai beginning of purchases in order to avoid problems of jammed bills of consumers. With the implementation of the right pricing strategy is expected to boost sales and increase profit company that product sales turnover PT Harapan Sentosa Raya Barabai increased and the company's target is reached.